Genomic evolution, recombination, and inter-strain diversity of chelonid alphaherpesvirus 5 from Florida and Hawaii green sea turtles with fibropapillomatosis - Morrison, Cheryl L.; Iwanowicz, Luke; Work, Thierry M.; Fahsbender, Elizabeth; Breitbart, Mya; Adams, Cynthia; Iwanowicz, Deb; Sanders, Lakyn; Ackermann, Mathias; Cornman, Robert S. (PeerJ, 2018)
Chelonid alphaherpesvirus 5 (ChHV5) is a herpesvirus associated with fibropapillomatosis (FP) in sea turtles worldwide. Single-locus typing has previously shown differentiation between Atlantic and Pacific strains of this virus, with low variation within each geographic clade. However, a lack of multi-locus genomic sequence data hinders understanding of the rate and mechanisms of ChHV5 evolutionary divergence, as well as how these genomic changes may contribute to differences in disease manifestation. To assess genomic variation in ChHV5 among five Hawaii and three Florida green sea turtles, we used high-throughput short-read sequencing of long-range PCR products amplified from tumor tissue using primers designed from the single available ChHV5 reference genome from a Hawaii green sea turtle. This strategy recovered sequence data from both geographic regions for approximately 75% of the predicted ChHV5 coding sequences. The average nucleotide divergence between geographic populations was 1.5%; most of the substitutions were fixed differences between regions. Protein divergence was generally low (average 0.08%), and ranged between 0 and 5.3%. Several atypical genes originally identified and annotated in the reference genome were confirmed in ChHV5 genomes from both geographic locations. Unambiguous recombination events between geographic regions were identified, and clustering of private alleles suggests the prevalence of recombination in the evolutionary history of ChHV5. This study significantly increased the amount of sequence data available from ChHV5 strains, enabling informed selection of loci for future population genetic and natural history studies, and suggesting the (possibly latent) co-infection of individuals by well-differentiated geographic variants.
Keywords: Green sea turtles; Fibropapillomatosis; Recombination; Protein divergence; Viral genomics; High-throughput sequencing; Phylogeography; Chelonid alphaherpesvirus 5